2020
DOI: 10.3892/ol.2020.12040
|View full text |Cite
|
Sign up to set email alerts
|

Sterically stabilized liposomes targeting P21 (RAC1) activated kinase‑1 and secreted phospholipase A<sub>2</sub> suppress prostate cancer growth and metastasis

Abstract: Metastatic prostate cancer (PCa) has a very high mortality rate in men, in Western countries and lacks reliable treatment. The advanced-stage PCa cells overexpress P21 (RAC1) activated kinase-1 (PAK1) and secreted phospholipase A 2 (sPLA 2) suggesting the potential utility of pharmacologically targeting these molecules to treat metastatic PCa. The small molecule, inhibitor targeting PAK1 activation-3 (IPA3) is a highly specific allosteric inhibitor of PAK1; however, it is metabolically unstable once in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In addition, SSLs are known to alter the pharmacokinetic profile of encapsulated drugs and improve their pharmacological activities [ 29 , 30 , 31 ]. Our studies showed that SSL-IPA-3 improved the stability of IPA-3 and improved its efficacy with regard to inhibiting prostate cancer growth both in vitro and in vivo [ 32 , 33 , 34 ]. While these studies focused on prostate cancer, we have also previously shown that the ability of SSL-IPA-3 to decrease cell growth was dependent on the expression of PAK-1 in a diverse set of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, SSLs are known to alter the pharmacokinetic profile of encapsulated drugs and improve their pharmacological activities [ 29 , 30 , 31 ]. Our studies showed that SSL-IPA-3 improved the stability of IPA-3 and improved its efficacy with regard to inhibiting prostate cancer growth both in vitro and in vivo [ 32 , 33 , 34 ]. While these studies focused on prostate cancer, we have also previously shown that the ability of SSL-IPA-3 to decrease cell growth was dependent on the expression of PAK-1 in a diverse set of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…This resulted in a novel formulation containing an increased level of 1,2-distearoyl- sn -glycero-3-phosphoethanolamine (DSPE). This formulation called secretory phospholipase responsive liposomes, or SPRL, was demonstrated to have increased efficacy in vitro and in vivo [ 34 , 35 ]. We further demonstrated that the increased efficacy was due, in part, to the increased selectivity for sPLA 2 [ 34 ], which was conferred by the inclusion of the anionic DSPE ( Table 1 ) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAK1 has in fact been shown to be essential for the growth of prostate cancer cells in a xenograft mouse model [ 86 , 89 ]. PAK1 contributes to prostate cancer cell growth and metastasis, due to its role in cell proliferation, survival, motility, invasion, and epithelial–mesenchymal transition (EMT) [ 90 , 91 , 92 , 93 ]. Inhibition of PAK1 is therefore promising for the treatment of this disease.…”
Section: Inhibition Of Pak1 For the Treatment Of Prostate Cancermentioning
confidence: 99%
“…Both SSL- and SPRL-IPA3 have markedly anti-proliferative effects on murine prostate cells (RM-1 cells). However, the free IPA3 had no significant therapeutic efficacy in the transgenic adenocarcinoma of the mouse prostate mice [ 90 ]. The authors found that this nanoparticle delivery system resulted in strong efficiency both in vitro and in vivo in the prostate cancer model, and that the drug showed strong specificity.…”
Section: Inhibition Of Pak1 For the Treatment Of Prostate Cancermentioning
confidence: 99%